Effect of sulfur dioxide (SO2) on growth and physiological activity in Alnus sieboldiana at Miyakejima Island in Japan. Issue 1 (28th November 2013) - Choi, Dongsu; Toda, Hiroto; Kim, Yongsuk
Abstract: We used a physiological approach to investigate the effect of sulfur dioxide (SO2 ) on Alnus sieboldiana Matsum. ( A. sieboldiana ) and symbiotic Frankia spp. in Miyakejima Island, which was devastated by volcanic action in July of 2000. In April of 2008, three study sites were chosen in the forest of Miyakejima Island, and were categorized as high, medium, or low in relation to their sulfur dioxide concentration (volcanic gas). Nine A. sieboldiana trees were selected from naturally regenerated forest at each site. The higher the SO2 concentration at the study site, the lower was the photosynthetic rate and the maximum photochemical efficiency of PSII ( F v / F m ) of A. sieboldiana and its apparent quantum yield. The acetylene reduction rate of the Frankia spp. symbiotic with A. sieboldiana was significantly less at the high SO2 concentration ( p <0.05). The nitrogen concentration in their leaves remained high, however. There was no significant difference in the chlorophyll concentration (Chl a + b ) in leaves from the three sites. The photosynthetic nitrogen use efficiency decreased significantly in sites with a high SO2 concentration, however. As a result, A. sieboldiana regenerated at the sites with high or medium SO2 concentration underwent approximately 50–70 % less growth than at the site with a low SO2 concentration.